The effect of phosphoric and phosphonic acid primers on bone cement bond strength to total hip stem alloys. (May 2017) - Jakubowitz, Eike; Liehn, Louisa; Jahnke, Alexander; Wöstmann, Bernd; Rickert, Markus; Niem, Thomas
Abstract: Aseptic loosening at alloy-cement interfaces constitutes a main failure mechanism of cemented total hip replacements (THR). As a potential solution we investigated the effect of metal primers containing phosphoric and phosphonic acid on shear bond strength (SBS) of bone cement to THR alloys (CoCrMo, TiAlNb) and pure tin (Sn) substrates (20×8×3 mm). Metal surfaces were modified by polishing or Al2 O3 blasting and primer application. Substrates without primer treatment served as references. Cylindrical cement pins (Ø 5 mm) were polymerised onto substrate surfaces and aging (1, 5, 14 and 150 days) was simulated in aqueous NaCl solution (0.9%) before SBS determination and failure mode evaluation. Regardless of surface roughness and aging time, SBS for THR alloys and Sn was always significantly higher with primer treatment. Compared to untreated reference specimens (≤0.2 MPa) SBS values increased even up to 350 fold (TiAlNb, 14 days) or 400 fold (CoCrMo, 5 days). In general, the phosphoric acid containing primer revealed significant higher SBS values on THR alloys compared to the phosphonic acid containing one. Al2 O3 blasted specimens showed generally higher SBS values than polished ones with the exception of Sn which showed high SBS values in general. With primer treatment on polished Sn a significant reduction of SBS could not be detected even up to 150 days, whereas THR alloys showed only an SBS improvement in the short term (≤14 days). A NaCl-pitting corrosion probably led to an increasing and durable SBS on polished Sn surfaces over time. Compared to modern THR in clinical practice that shows survival rates of 10, 15, 20 or more years, the receivable bond strength enhancements described in this study appeared to be very short. The improved SBS on THR alloys lasted only a few days before it was lost again. In contrast, the phosphoric acid primer treatment of polished Sn appeared to be very promising and may play a key role in further investigations dealing with the prevention of the stem-cement debonding in THR.